Allosteric Modulation of Human Serum Albumin Induced by Peptide Ligand. Issue 8 (9th June 2017) - Hou, Jingfei; Peng, Jiaxi; Yu, Yue; Lin, Yuchen; Liu, Changliang; Duan, Hongyang; Yang, Yanlian; Wang, Chen
Abstract : Human serum albumin (HSA) is an abundant protein in plasma that can bind and transport many small molecules, and the corresponding affinity‐controlled drug delivery shows great advantage in the biological system. Peptide SA06 is a reported ligand comprising 20 amino acids, and is known to non‐covalently bind with HSA to extend the lifetime and improve the pharmacokinetic performance. The structural information of the HSA‐peptide complex is keen for obtaining molecular insight of the binding mechanism. We studied the secondary structural change and structure‐affinity relations of Peptide SA06 with HSA by using circular dichroism (CD) spectroscopy in solution. Noticeable allosteric effect can be identified by compositional increase of α ‐helix structures when the peptide was co‐incubated with HSA. Furthermore, the equilibrium dissociation constant of Peptide SA06 with HSA can be determined by CD‐based method. This work provides structural evidence on the allosteric interaction between peptide ligand and HSA, and sheds light on optimization of therapeutic properties in the affinity‐controlled delivery systems. Abstract : This work studied allosteric modulation of human serum albumin induced by peptide ligand, figured out the binding affinity, and provided structural evidence on the interaction mechanism of albumin‐peptide complex.